Choice Matters: Responses to Political Information Vary in Randomized vs. Selective Exposure Contexts. Issue 2 (4th March 2022) - Fernandes, Juliana; Lewis, Nicky; Hong, Cheng
ABSTRACT: Three studies (study 1, 2a and 2b) were conducted to examine the effects of exposure type (randomized, selective) to negative and positive political information. Study 1 focused on a randomized exposure situation whereas study 2a and 2b investigated selective exposure conditions. Participants ( N  = 274 for study 1, N = 197 for study 2a, and N = 197 for study 2b) were recruited on Amazon Mechanical Turk. Drawing from the literature on negativity bias and socioemotional selectivity theory (SST), we found young individuals, as compared to older individuals, were more affected by negative political information, but only when exposure to the information was randomized. When given the opportunity for selective exposure to positive, negative, or neutral political information, effects associated with SST and the negativity bias were weakened while effects associated with political uses and approaches were bolstered. Implications as to how different types of exposure to negative and positive political information influence responses to information and their relation to SST, negativity bias, and uses and gratifications are discussed.